Television studies - Gray, Jonathan; Lotz, Amanda D. 1974- (Polity, 2019)
"Television Studies provides an overview of the origins, central ideas, and intellectual traditions of television studies. For all those wondering how to study television, or even why to study television, this new edition will provide a clear and engaging overview of key topics"-- Provided by publisher.